Analisis Ruang Lingkup Studi Al Qur’an Cabang Kajian Keterkaitan dengan Ilmu Tafsir - Totussangadah, Robit; Ahmad Kafi Hamdi (Midaduna: Journal of Islamic Studies, 2024)
This paper aims to find out the scope, branches of study, and the relationship between Qur'anic Studies and the science of Tafsir. This research is a type of library research with content analysis. The results of this study show: 1) The scope of Qur'anic studies includes aspects of linguistics, history, and Islamic law; 2) Branches of study include Qur'anic sciences such as Science of al-Qira'at, Science of al-Tafsir, and Science of al-Hadith; 3) The relationship between Ulum al-Qur'an and the science of Tafsir includes contextual understanding, hermeneutics, and tafsir methodology.